Fatty acid esters of azaspiracids identified in mussels (Mytilus edulis) using liquid chromatography-high resolution mass spectrometry. (December 2020) - Mudge, Elizabeth M.; Miles, Christopher O.; Hardstaff, William R.; McCarron, Pearse
Abstract: Azaspiracids (AZAs) are lipophilic polyether toxins produced by Azadinium and Amphidoma species of marine microalgae. The main dinoflagellate precursors AZA1 and AZA2 are metabolized by shellfish to produce an array of AZA analogues. Many marine toxins undergo fatty acid esterification in shellfish, therefore mussel tissues contaminated with AZAs were screened for intact fatty acid esters of AZAs using liquid chromatography-high resolution mass spectrometry. Acyl esters were primarily observed for AZAs containing hydroxy groups at C-3 with 3- O -palmitoylAZA4 identified as the most abundant acyl ester, while other fatty acid esters including 18:1, 16:1, 17:0, 20:2 and 18:0 acyl esters were detected. The structures of these acyl derivatives were determined through LC-MS/MS experiments, and supported by periodate cleavage reactions and semi-synthesis of palmitate esters of the AZAs. Esters of the hydroxy groups at C-20 or C-21 were not observed in mussel tissue. The relative proportion of the most abundant AZA ester was less than 3% of the sum of the major free AZA analogues. These findings reveal an additional metabolic pathway for AZAs in shellfish. Highlights: Fatty acid esters of azaspiracids were identified in mussels (Mytilus edulis ). Fatty acid esters of azaspiracids with hydroxy groups at C-3 were primarily observed. Fatty acid esters of regulated azaspiracids (AZA1, 2, −3) were absent. Structures were determined with LC-HRMS and confirmed by semi-synthesis of palmitate esters and periodate cleavage. This work reveals an additional metabolic pathway for azaspiracids in shellfish.